Of Slight, Spite, and Suspicion: The Treatment of India in E. M. Forster’s A Passage to India - Debashish Biswas; Samia Yesmin; Prakash Chandra Biswas (WISE Pendidikan Indonesia, 2025)
This study analyzes E. M. Forster’s A Passage to India through the lens of colonial psychology, examining the intricate dynamics between the British colonizers and the Indian populace. The research focuses on the recurring themes of